Արևմտահայության կոտորածների կանխմանն ուղղված Գևորգ Ե Սուրենյանցի գործունեությունը (1915 թ. ապրիլ-նոյեմբեր) - Ամիրջանյան, Հասմիկ Հ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В 1908 г., когда в Османской империи младотурки пришли к власти, преследование армян не прекращалось. С начала апреля 1909 г. турки организовали погромы армян Киликии. Католикос всех армян Геворг V, сыгравший большую роль в раскрытии Армянского вопроса в 1912, получил информацию из разных источников о массовых убийствах армян в Западной Армении. Католикос обратился к разным европейскими и российскими государственными военным и общественным деятелям с просьбой предотвратить резню западных армян. Целью католикоса было заставить турецкое правительство прекратить резню через вмешательство великих держав. Однако европейские державы и российское правительство ограничивались лишь дипломатическими шагами и обещаниями, руководствуясь собственными интересами․ In 1908, after the abolition of Abdul-Hamid’s despotic regime and the coming to power of the Young Turks, the persecutions and atrocities against the Western Armenians did not stop. From Аpril 1909 the Turks organized the massacre of the Armenians of Cilicia. The Catholicos of All Armenians, Gevorg V, who played a major role in the discovery of the Armenian question in 1912, received information about the massacre of Armenians in Western Armenia from various sources. The Catholicos appealed to various state and public European and Russian statesmen and public figures with the request to prevent the massacre of the Western Armenians. The purpose of the Catechism was to influence the Turkish government through the great powers and make them stop the massacre. However, the European countries and the Russian government, guided by their own interests, were limited to diplomatic steps and promises.
Keywords: Պատմություն